1995
DOI: 10.1002/j.1460-2075.1995.tb07248.x
|View full text |Cite
|
Sign up to set email alerts
|

Biochemical and genetic analysis of the Drk SH2/SH3 adaptor protein of Drosophila.

Abstract: T.Raabe and J.P.Olivier contributed equally to this work The Drk SH3-SH2-SH3 adaptor protein has been genetically identified in a screen for rate-limiting components acting downstream of the Sevenless (Sev) receptor tyrosine kinase in the developing eye of Drosophila. It provides a link between the activated Sev receptor and Sos, a guanine nucleotide release factor that activates Rasl. We have used a combined biochemical and genetic approach to study the interactions between Sev, Drk and Sos. We show that Tyr2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(63 citation statements)
references
References 51 publications
4
59
0
Order By: Relevance
“…In flies, it was first identified and characterized in the context of signaling from the Sevenless receptor tyrosine kinase, where it links the phosphorylated receptor at the plasma membrane (by its SH2 domain) to the Ras guanine-exchange-factor Sos (by its SH3 domain). Ras activation then leads to the activation of a phosphorylation cascade of MAPK kinase (Raf) and Rolled, the Drosophila homolog of ERK and MAPK (Biggs et al, 1994;Olivier et al, 1993;Raabe et al, 1995;Simon et al, 1991). Based on our analysis and on previously published work, we propose that the predominant role of Drk in wound healing is to mediate ERK activation and the transcriptional induction of woundresponse genes (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…In flies, it was first identified and characterized in the context of signaling from the Sevenless receptor tyrosine kinase, where it links the phosphorylated receptor at the plasma membrane (by its SH2 domain) to the Ras guanine-exchange-factor Sos (by its SH3 domain). Ras activation then leads to the activation of a phosphorylation cascade of MAPK kinase (Raf) and Rolled, the Drosophila homolog of ERK and MAPK (Biggs et al, 1994;Olivier et al, 1993;Raabe et al, 1995;Simon et al, 1991). Based on our analysis and on previously published work, we propose that the predominant role of Drk in wound healing is to mediate ERK activation and the transcriptional induction of woundresponse genes (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…In both cases, we detected a substantial decrease in SOCS36E immunoprecipitation. This suggests the requirement of the SH2 domain and Tyr2546 phosphorylation to achieve the interaction, similarly to the situation with Drk (Raabe et al, 1995) (Fig. 3A).…”
Section: Direct Interaction Between Sev and Socs36ementioning
confidence: 52%
“…It has been previously reported that Drk interacts specifically with the phosphorylated tyrosine residue 2546 (Tyr2546) of activatedSev RTK through its SH2 domain (Raabe et al, 1995). A direct interaction between Drk/Grb2 and another RTK, EGFR, has also been described in mammals (Sorkin et al, 2000).…”
Section: Direct Interaction Between Sev and Drkmentioning
confidence: 99%
“…BmHOP is a tyrosine kinase that is activated via phosphorylation by the transcription factor BmSTAT and is polymerized into dimers that interact with a downstream gene (Lin et al, 2004). BmDRK is a receptor kinase of the downstream part of the JAK-STAT pathway and BmSOCS is a negative regulator (Cooney, 2002;Raabe et al, 1995). A series of reports suggested that these five proteins play an important role in JAK-STAT-mediated immune responses (Geng et al, 2016;Liu et al, 2013Liu et al, , 2015.…”
Section: Introductionmentioning
confidence: 99%